Degree of Completion of 3′-Terminus of Transfer Ribonucleic Acids of Bacillus subtilis 168 at Various Developmental Stages and Asporogenous Mutants - Vold, Barbara (1974)
Transfer ribonucleic acids from sporulating cells, spores, sporangia, or stationary-phase asporogenous mutants of Bacillus subtilis all showed a deficiency in the 3′-terminal adenosine moiety.